ANALYSIS OF THE VARIATION OF THE ROUGHNESS OBTAINED DURING TURNING WITH TRANSVERSE FEED DUE TO THE MODIFICATION OF THE FUNCTIONAL GEOMETRY OF THE CUTTING TOOL - Mădălin TOMESCU; Ionela Magdalena ROTARU (Fiabilitate şi Durabilitate)
The role of machining by chipping is to generate surfaces that must correspond to the requirements imposed by the designer through the execution drawing of the part. The quality of the surface of a part is a very complex notion and includes two aspects: the geometry of the superficial layer, which determines the deviations of the real surface from the theoretical surface and the roughness (micro-irregularities) of the real surface and the condition of the superficial layer of the processed surface from a physical point of view (degree of deformation, residual stresses, thermal, chemical, thermochemical treatments, etc.). From the point of view of machining by chipping, the first aspect is very important and in particular the surface roughness. The paper aims to analyze how the surface roughness evolves as a result of the variation of the functional geometry of the tool when turning with transverse feed. The turning technological process with transverse feed is carried out with a variable cutting speed, and this also determines a variation of the tool's functional geometry. Thus, in the work, the optimal constructive geometry of a lathe knife that can be used for turning a piece with a diameter was established 150mm . Under these conditions, a correlation was identified between the values of the functional geometric parameters of the cutting tool knife used for transverse turning of C45 (1.0503) steel: EN 10277-2-2008- 150mm .and roughness (surface quality).